Peran Sumber Daya Alam Sebagai Penggerak Perekonomian Nasional: Penelitian - Bonaraja Purba; Adel Syesaria Agustin Daole; Ledi Marina Purba; Selpiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to examine the contribution of natural resources (NR) to Indonesia’s national economy. The study employs a descriptive qualitative method with Indonesia as a case study, using secondary data obtained from official government publications, the Central Bureau of Statistics (BPS), the Ministry of Energy and Mineral Resources, as well as relevant academic literature. The findings indicate that natural resources play a significant role in supporting gross domestic product (GDP), exports, state fiscal revenues, and employment, both directly and indirectly, through multiplier effects on the transportation, logistics, and financial services sectors. Overall, the study concludes that natural resources remain a key driver of national development; however, they must be managed with principles of sustainability, equitable distribution of benefits, and technological advancement.